Endogenous sex hormone levels are associated with the revised Framingham Stroke Risk Profile in postmenopausal women: a longitudinal study in a Swedish cohort - Kristin Ottarsdottir; Åsa Tivesten; Claes Ohlsson; Ying Li; Margareta Hellgren; Ulf Lindblad; Bledar Daka (BMC Endocrine Disorders)
Abstract Background Endogenous sex hormones in postmenopausal women have been associated with risk of cardiovascular diseases. The aim of this study was to determine the association between endogenous sex hormones and the revised Framingham Stroke Risk Profile (rFSRP) in postmenopausal women. Methods This is an observational cross-sectional study on the Vara-Skövde cohort, a Swedish population-based study for longitudinal surveillance of the development and progress of type 2 diabetes and hypertension. The participants were physically examined in 2002–2005 and sex hormones were analysed with liquid chromatography-tandem mass spectrometry assay (LC-MS/MS). Women who were ≥55 years old, with estradiol levels below 20 pg/mL, not using hormonal therapy, and with no self-reported history of stroke, were included (N = 133). The outcome variable was rFSRP. Regression analyses of log-transformed rFSRP were fitted against levels of sex hormones (17-α-OH-progesterone, estrone, estradiol, progesterone, dihydrotestosterone, dehydroepiandrosterone, testosterone and androstenedione), adjusting for body mass index (BMI) or waist-to-hip ratio (WHR), C-reactive protein (CRP) and cholesterol level. Results Levels of estrone and estradiol were positively associated with rFSRP in the crude model (estrone β = 0.208, 95% CI = 0.081;0.336, P = 0.002; estradiol β = 0.170, CI = 0.034;0.305, P = 0.015). Adjustments for BMI revealed significant positive associations between progesterone (β = 0.155 95% CI = 0.025;0.285, P = 0.020), estrone (β = 0.167, 95% CI = 0.037;0.297, P = 0.013) and 17-α-OH-progesterone (β = 0.146, 95% CI = 0.014; 0.277, P = 0.030) and rFSRP, and adjustments for WHR revealed a significant positive association between testosterone and rFSRP (β = 0.152, CI = 0.026;0.278, p = 0.018). Conclusions Increase of estrone was associated with higher rFSRP, also in the fully adjusted model, whereas progesterone, 17-α-OH-progesterone and testosterone were significant only in the models adjusting for BMI and WHR respectively. Larger studies studying stroke events are warranted to confirm these findings. Clinical trial number Not applicable.